Sodium selenite as a new rodenticide - Jokić, Goran; Vukša, Marina; Đedović, Suzana; Šćepović, Tanja; Jaćević, Vesna; Stojnić, Bojan (Pesticidi i fitomedicina, 2014)
Rodents are the most destructive group of small mammalian pests considering the overall damage that they cause by feeding and other activities, or as vectors of many disease agents. In practice, chemical rodenticides have been the most widespread and most effective method of control of commensal (Mus musculus, Rattus norvegicus and R. rattus) and most harmful field rodent pests (Apodemus sylvaticus, A. agrarius and Microtus arvalis). After anticoagulant and vitamin D3 rodenticides, which were introduced worldwide in the 1980s, no other chemical compound has had a comparable role as a rodenticide in practice. In the past decade, commercial baits containing 0.1% sodium selenite have also been registered in Serbia in various formulations both for controlling rodents indoors and in the field. Data on sodium selenite as a rodenticide have been scarce. The present paper surveys research data reported so far, analyzing and drawing conclusions regarding the validity and feasibility of sodium selenite as a method of rodent control with reference to the available ecotoxicological data. U odnosu na ukupnu štetnost koju nanose ishranom i drugim aktivnostima, ali i kao prenosioci većeg broja prouzrokovača različitih obolenja, glodari spadaju u najštetnije vrste sitnih sisara. U praktičnim uslovima primene, rodenticidi hemijskog porekla predstavljali su najprimenljiviji i najefektniji način suzbijanja štetnih komensalnih (Mus musculus, Rattus norvegicus and R. rattus) kao i najštetnijih vrsta poljskih glodara (Apodemus sylvaticus, A. agrarius, Microtus arvalis). U odnosu na antikoagulantne rodenticide i vitamin D3, koji su uvedeni u primenu do 80-ih godina prošlog veka, u svetu, u praktičnim uslovima primene, ni jedno novo jedinjenje nije zauzelo značajniju ulogu kao rodenticid. Proteklih desetak godina u našoj zemlji registrovani su i komercijalno dostupni mamci sa sadržajem 0.1% natrijum selenita, različitih formulacija, kao rodenticidi za suzbijanje glodara u zaštićenim i uslovima otvorenog polja. Za sada je malo ...